2022
DOI: 10.1038/s41598-022-06991-1
|View full text |Cite
|
Sign up to set email alerts
|

Size fractionation of high-density polyethylene breakdown nanoplastics reveals different toxic response in Daphnia magna

Abstract: Plastic litter is a growing environmental problem. Recently, microplastics and nanoplastics, produced during breakdown processes in nature, have been in focus. Although there is a growing knowledge concerning microplastic, little is still known about the effect of nanoplastics. We have showed that mechanical breakdown of high-density polyethylene (HDPE), followed by filtration through 0.8 µm filters, produces material toxic to the freshwater zooplankton Daphnia magna and affected the reproduction in life-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Recent observations that the hazard of aging microplastics may be predominantly attributed to the released DOC add to the relevance of identifying recalcitrant species in the DOC. 79 This would extend our understanding of microplastics' environmental fate beyond observations from residual polymer and could support (i) the design of new materials, e.g., exploiting physicochemical properties that allow polymer and by-products to be (bio)degradable, and (ii) regulatory efforts, e.g., by limiting the production and application of polymers that release persistent or toxic DOC.…”
Section: Discussionmentioning
confidence: 99%
“…Recent observations that the hazard of aging microplastics may be predominantly attributed to the released DOC add to the relevance of identifying recalcitrant species in the DOC. 79 This would extend our understanding of microplastics' environmental fate beyond observations from residual polymer and could support (i) the design of new materials, e.g., exploiting physicochemical properties that allow polymer and by-products to be (bio)degradable, and (ii) regulatory efforts, e.g., by limiting the production and application of polymers that release persistent or toxic DOC.…”
Section: Discussionmentioning
confidence: 99%
“…The emission sources as well as the impact of NPLs in the environment remain largely unknown mainly due to the limitations concerning the characterization and identification of small carbon-based particles in complex matrices [15] . In this context, studies are increasingly addressing the potential release of primary and secondary NPLs under relevant conditions.…”
Section: Source and Occurrence Of Npls In Freshwater Environmentsmentioning
confidence: 99%
“…There is no agreement within the scientific community regarding the upper limit of this size range. Some authors use the limit of 100 nm [15,16] , while others prefer 1000 nm [17,18] . There are reasons to support any of these definitions based on analytical limitations or colloidal behavior in water suspension, but a detailed discussion is outside the scope of this review.…”
Section: Introductionmentioning
confidence: 99%
“…Ekvall et al also recently reported on nanoplastics of high-density polyethylene displaying a diameter around 110 nm which induced a size-dependent toxic effect in the zooplankton species Daphnia magna. [16] In their method, the prepared polyethylene particles were not stable in solution over time, that is, no nanoparticles were detected after a storage time of 100 days. Very likely, their 𝜁 potential of about −10.9 ± 6.4 mV was not sufficient to allow for colloidal long-term stability.…”
Section: Introductionmentioning
confidence: 99%